2014
DOI: 10.1016/j.rbmo.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Is there a critical endometrioma size associated with reduced ovarian responsiveness in assisted reproduction techniques?

Abstract: This study investigated the relationships between ovarian endometrioma size, ovarian responsiveness and the number of retrieved oocytes following ovarian stimulation. A prospective study was conducted in a public clinical assisted reproduction centre. A total of 64 infertile women with monolateral endometriomas undergoing IVF or intracytoplasmic sperm injection were included in the study. The total number of follicles, number of follicles ≥ 16 mm and number of oocytes retrieved of ovaries containing endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 49 publications
(64 reference statements)
1
38
0
Order By: Relevance
“…The management of endometriomas that are <40 mm in size in women who attempt to conceive remains a matter of debate 5, 13, 14, 15. The results of this study demonstrated that the AFC, the number of follicular flushings, the number of retrieved oocytes, and the number of obtained embryos were all significantly lower for the endometrioma‐containing ovary than for the contralateral, intact ovary.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The management of endometriomas that are <40 mm in size in women who attempt to conceive remains a matter of debate 5, 13, 14, 15. The results of this study demonstrated that the AFC, the number of follicular flushings, the number of retrieved oocytes, and the number of obtained embryos were all significantly lower for the endometrioma‐containing ovary than for the contralateral, intact ovary.…”
Section: Discussionmentioning
confidence: 71%
“…Another study also reported that the presence of an endometrioma resulted in a reduced response to ovarian stimulation, compared with the response of the contralateral, intact ovary in the same individual. It also was found that, in the case of endometriomas that are <30 mm, the basal FSH concentration is the most important prognostic factor for oocyte retrieval 14. In contrast, it has been reported that the presence of an endometrioma is not associated with a reduction in the number of retrieved oocytes 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ESHRE guidelines, laparoscopic surgery before IVF/ICSI is considered to be the 'gold standard' in the treatment of symptomatic endometriomas (12). On the other hand, surgery indeed has a detrimental impact on ovarian reserve in terms of serum AMH levels and overall response to OS (15)(16)(17), despite enough surgical experience (26)(27)(28). In this context, size of the endometrioma seems to be the crucial determinant in management.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the pregnancy rate was similar between the groups [23].These results argue against excision of an endometrioma in women scheduled for IVF as surgery does not appear to improve the chance of pregnancy. Nevertheless, all endometriomas are not the same, and it appears that cysts over 3 cm have a more severe impact on ovarian performance during COH [24]. Moreover, such large endometriomas may restrict vaginal access to the ovary during retrieval.…”
Section: In Vitro Fertilizationmentioning
confidence: 99%